ANALISIS PENGARUH KUALITAS PELAYANAN, FASILITAS DAN NILAI PELANGGAN TERHADAP KEPUASAN PASIEN (STUDI PADA PASIEN RUANG RAWAT INAP RUMAH SAKIT PKU MUHAMADIYAH GOMBONG) - Siswanto, Dimas; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2019)
This study aimed to: 1, analyze the influence of service quality factors on hospital patientsatisfaction, 2, analyze the influence of facility factors on hospital patient satisfaction, and 3,analyze the influence of customer value factors on hospital patient satisfaction.This study used a sample of 100 people. The type of data in this study is to use two data,namely primary and secondary data. The primary data sources used in this study arequestionnaires and interviews with respondents about the effect of service quality, facilities, andcustomer value on customer satisfaction. While the secondary data is newspapers, books, journals,the internet. The data analysis model in this study uses the instrument test, classic assumption test,and hypothesis testing using Linear Regression Analysis with the help of SPSS software.The results showed that the quality of service, facilities, and customer value towards thesatisfaction of patients in PKU Muhamadiyah Gombong hospital both partially and simultaneouslyor together with a contribution of 61.2% and the remaining 38.8% patient satisfaction wasinfluenced by other factors that were not examined in this study.